Perceptions of library and information science community towards open source software adoption in libraries of Oman - Saleh, al Zeheimi; Zeki, Akram M.; Mohamed Razi, Mohamed Jalaldeen; Zain, Samer M.; Abubakar, Adamu (2014)
This paper undertake a focus group research approach to investigate the perceptions of LIS community towards open source software adoption in libraries of Oman. The motivation of the study comes as a result of E-Oman strategy to uplift the information and communication technology services in Oman. The focus group approached applied in this study was carried out by means of inviting participants from seven institutions in Oman, to participate in a workshop about OSS adoption in libraries. During the workshop, focus groups were established. After the workshop, each group participates in responding to their perception towards OSS adoption in libraries. The results of their responses were analyzed. It was discovered that there are lack of awareness and readiness toward adoption of open source software in libraries of Oman.